Determination of Total Phenolic and Flavonoid Contents and Evaluation of Antioxidant Activity of an Algerian Medicinal Species, Arbutus serratifolia Salisb: Arbutus serratifolia Salisb - Belattar, Nadjah; Sarri, djamel; Ikhlef, Fatima; Bensouici, Chawki; Seghiri, Ramdane; Benayache, Samir; Benayache, Fadila; Mekkiou, Ratiba (Iranian Journal of Pharmaceutical Sciences, 2023)
Arbutus serratifolia Salisb. is known as a strawberry tree belonging to the Ericaceae family and represents a Mediterranean evergreen shrub. The species distributed in the forest of El Milia region (Jijel) was chosen as a specimen for chemical investigation and biological evaluation for the first time from this region. The MeOH extract of the aerial parts underwent qualitative phytochemical screening using conventional techniques. While CHCl3, EtOAc, n-BuOH, and even MeOH fractions were subjected to quantitatively determine the total phenolic and flavonoid contents using the Folin-Ciocalteu and Aluminium trichloride methods respectively. The antioxidant potential of these fractions was assessed using the DPPH scavenging activity, ABTS cation radical reduction, CUPRAC reducing capacity and Phenanthroline assays. This study revealed that A. serratifolia Salisb. fractions are endowed with potent antioxidant activity; thus, it is worth noting that this plant could be used as a rich food source for a wide range of phenolic compounds, particularly of new antioxidant agents.